(untitled) (Research, Society and Development, 2023)
This study evaluated the influence of maternal diabetes on the reproductive outcomes of adult daughters during full-term pregnancy in rats. The local ethics committee approved all experimental protocols. The adult female pups of nondiabetic (control – CP) and diabetic (DP) mothers were subjected to mating with healthy male rats for reproductive analysis. On day 17 of pregnancy, both groups underwent an oral glucose tolerance test (OGTT) to evaluate glucose tolerance. At the end of pregnancy, the rats were anesthetized for laparotomy and exposure of maternal organs. Uterine horns, ovaries, fetuses, and placentas were weighed to classify fetal weight and placental efficiency. P<0.05 was considered a statistically significant limit, and Pearson’s correlation was used. Higher maternal fasting blood glucose was correlated with a lower number of live fetuses and, consequently, with a lower litter weight. Thus, maternal fasting glucose during pregnancy is a relevant biomarker related to the poor reproductive outcome of daughters of rats. Furthermore, these findings show the detrimental effects of fetal programming induced by maternal diabetes in adulthood in the subsequent generation.